Risk assessment on contractors' pricing strategies - Xu, Tian Ji. (2011)
In competitive tendering, pricing strategies are used to facilitate the contractors' cash-flows. Often the decisions are based on contractors' experiences, intuitions, and personal bias. Inevitably, an unexpected deficit may become inherent risks of the project. A new approach, risk assessment on contractors' pricing strategies is presented in this dissertation. Existing mark-up or cash-flow forecasting models simulate the pricing strategies in a simplified manner which may depart from real world and therefore, lead the inaccurate cash-flow forecasting. The models could hardly quantify risks associated with pricing strategies. In real world, the quantities of break-down cost items are random variables. The approach developed here enables the contractor to find the global optimal pricing through the stochastic programming model. Further, the risks caused by contractors' pricing strategies are assessed by risk identification and risk quantification. A real case analysis using the approach is shown. Finally, the risk control issues are discussed.